2007
DOI: 10.2527/jas.2006-237
|View full text |Cite
|
Sign up to set email alerts
|

Changes in small intestinal nutrient transport and barrier function after lipopolysaccharide exposure in two pig breeds1

Abstract: Specific pig breeds with unique characteristics have been developed, and the current study sought to characterize some of these differences. Using modified Ussing chambers, electrophysiological mucosal transport of D-glucose, L-Gln, L-Pro, L-Arg, L-Thr, and glycylsarcosine was assessed in small intestinal tissues (duodenum, jejunum, ileum) taken from Yorkshire-based hybrid (BW = 142.4 +/- 2.0 kg; mean age = 8 mo) and Meishan (BW = 65.8 +/- 0.8 kg; mean age = 6 mo) female pigs after 4 h of lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…This similarly fits with our data as we see greater permeability at 6 h in the ileum compared to colon. The magnitude of the TER change we observed was somewhat similar to a previous study in large size pigs (Albin et al, 2007). Histologically, as little as 30 min of severe HS (41.5-42°C) has been shown to cause sloughing of villi tips and, by 60 min, entire epithelial sheets sloughing as well as denuded villi in rodents (Lambert et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…This similarly fits with our data as we see greater permeability at 6 h in the ileum compared to colon. The magnitude of the TER change we observed was somewhat similar to a previous study in large size pigs (Albin et al, 2007). Histologically, as little as 30 min of severe HS (41.5-42°C) has been shown to cause sloughing of villi tips and, by 60 min, entire epithelial sheets sloughing as well as denuded villi in rodents (Lambert et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…It has been demonstrated that the altered intestinal permeability reflecting intestine barrier integrity was associated with LPS challenge in pigs [34]. LPS-induced lung inflammation was also demonstrated to be associated with increased epithelial permeability in rats [35].…”
Section: Discussionmentioning
confidence: 98%
“…The decrease in NO production contributes to the decrease in superior mesenteric blood flow in the piglets and induction of mucosal atrophy (31). Arg supplementation effectively improves intestinal barrier function and vascular development in adult pigs (32), and many rodent models have demonstrated increased intestinal recovery after ischemia-reperfusion injury when Arg is supplemented (33,34). Puiman et al (35) demonstrated that partial EN does increase blood flow compared with TPN-fed piglets, but enteral physiological or pharmacological doses of Arg do not increase superior mesenteric artery blood flow.…”
Section: Introductionmentioning
confidence: 99%